Asymmetric Synthesis of (1, 5)Naphthalenophanes by Dehydro‐Diels–Alder Reaction. Issue 11 (21st February 2013) - Wessig, Pablo; Matthes, Annika; Schilde, Uwe; Kelling, Alexandra
Abstract: An asymmetric variant of the dehydro‐Diels–Alder (DDA) reaction has been developed and applied in the atropselective synthesis of various (1, 5)naphthalenophanes. Whereas the suitability of the photochemically induced DDA (PDDA) was limited, the thermally induced DDA provided the desired product, depending on the chiral auxiliary used and the length of the linker, with nearly perfect stereoselectivity. Furthermore, the mechanism of the DDA was investigated by means of DFT calculations, and a stepwise mechanism involving 1, 4‐biradicals was suggested. Abstract : The asymmetric dehydro‐Diels–Alder (ADDA) reaction to axially chiral (1, 5)naphthalenophanes was investigated. Using chiral auxiliaries, both photochemical and thermal DDA provided the target compounds, in which the latter approach provided better results in regard to yields and stereoselectivity. Furthermore, the mechanism of the DDA reaction was investigated by means of DFT calculations.